2021
DOI: 10.1053/j.gastro.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Age to Stop Endoscopic Surveillance of Patients With Barrett’s Esophagus Based on Sex and Comorbidity: A Comparative Cost-Effectiveness Analysis

Abstract: BACKGROUND AND AIMS: Current guidelines recommend surveillance for patients with nondysplastic Barrett’s esophagus (NDBE) but do not include a recommended age for discontinuing surveillance. This study aimed to determine the optimal age for last surveillance of NDBE patients stratified by sex and level of comorbidity. METHODS: We used 3 independently developed models to simulate patients diagnosed with NDBE, varying in age, sex, and comorbidity level (no, mild, moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…From a pragmatic perspective, it is reasonable to cease endoscopic surveillance in patients with an estimated survival of less than 5 years and those who are no longer fit for repeated endoscopy or cannot tolerate endoscopic, surgical, or oncological intervention for esophageal neoplasia. A recent modeling study suggested that the optimal age of last surveillance of a patient with NDBE was between 69 and 81 years and was dependent on the sex and comorbidities of the patient (125). Although it is difficult to be dogmatic given the wide variability in life-limiting comorbidities, given the current average American life expectancy, discussion of cessation of further endoscopic surveillance is merited when most patients reach 75 years of age, if it has not occurred prior.…”
Section: Management Of Be With Lgd or Hgdmentioning
confidence: 99%
“…From a pragmatic perspective, it is reasonable to cease endoscopic surveillance in patients with an estimated survival of less than 5 years and those who are no longer fit for repeated endoscopy or cannot tolerate endoscopic, surgical, or oncological intervention for esophageal neoplasia. A recent modeling study suggested that the optimal age of last surveillance of a patient with NDBE was between 69 and 81 years and was dependent on the sex and comorbidities of the patient (125). Although it is difficult to be dogmatic given the wide variability in life-limiting comorbidities, given the current average American life expectancy, discussion of cessation of further endoscopic surveillance is merited when most patients reach 75 years of age, if it has not occurred prior.…”
Section: Management Of Be With Lgd or Hgdmentioning
confidence: 99%
“…Despite this, some professional organizations (eg, American College of Gastroenterology [ACG], American Society for Gastrointestinal Endoscopy) recommend screening and surveillance for Barrett esophagus. A recent analysis suggested that when determining whether to perform screening or surveillance, the patient’s overall life expectancy (<10 years) should be considered …”
Section: Evaluating Patients For Barrett Esophagusmentioning
confidence: 99%
“…While 90% or more of the BE surveillance population has NDBE, representing the majority of a gastroenterologist’s typical BE caseload. [ 32 ] NDBE patients harbors many patients who require proactive management.…”
Section: Discussionmentioning
confidence: 99%